Producing Brazilianess for Global Audiences: The case of Sex and the City - Nogueira JOYCE, Samantha; LA PASTINA, Antonio C. (Ação Midiática – Estudos em Comunicação, Sociedade e Cultura, 2014)
This paper examines how the HBO series Sex and the City (SATC) portrayed “Brazilianess” during its six-season run. Although the program was recognized for its positive portrayal of female friendship and was usually praised for its association with female empowerment through story line, sexually explicit dialogue, and their successful careers we demonstrate how when it comes to Brazilianess and Brazilians, the program relied on stereotypical non-empowering and somewhat unrealistic portrayals. As Brazilian scholars and feminists we hope to question and explore the ways that Brazilianess, is portrayed in United States media more broadly and television specifically. We are focusing on Brazilianess in an attempt to move away from character specific analysis to question how Brazil as a nation and a culture, but also as a space where practices are performed, is produced in U.S. television shows such as SATC. Although research on the representation of Brazilians on Brazilian media is ample the same is not true when it comes to U.S. media. This essay seeks to begin to fill this gap.